(untitled) (TERRA LATINOAMERICANA, 2025)
The biodegradation of vulcanized rubber is an environmental challenge due to its high resistance to decomposition. This study evaluated the ability of three lignocellulolytic fungal strains (Phlebiopsis sp., Trametes sanguinea, and Trametes cingulata) to degrade tire powder in a liquid medium, selecting these strains for their prior ability to degrade toxic compounds such as xylene. The results highlighted Phlebiopsis sp. as the most ef fective strain, with a notable 43.163% reduction in rubber content in the treatment with 75% rubber and 25% PDB (T2). T. sanguinea also showed significant performance, with a 9.58% reduction in the same treatment. These results underscore the potential of these strains for rubber bioremediation, a material known for its environmental persistence. FTIR spectroscopy confirmed that both Phlebiopsis sp. and T. sanguinea caused structural modifications in the rubber, showing a decrease in signals associated with the functional groups of rubber and carbon black. This demonstrates that these fungi can alter the chemical structure of rubber, facilitating its degradation. This study highlights the importance of selecting specific strains for industrial bioremediation. Phlebiopsis sp. emerges as an up-and-coming option due to its high degradation capacity. T. sanguinea, although less ef fective, also presents considerable potential. These findings are crucial for developing ef fective strategies for managing rubber waste and suggest that future research should focus on optimizing cultivation conditions and exploring the enzymatic mechanisms of these strains.